Cryptogenic stroke in atrial fibrillation without intra-heart thrombi: possible mechanisms - O. A. Germanova; A. V. Germanov; G. Galati; I. O. Prokhorenko; V. A. Germanov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2022)
Background. Up to 45% of ischemic strokes are cryprogenic.Aim is to study which variant of permanent AF without intra-heart thrombi is the most unfavorable in appearing of stroke.Methods. We observed 202 patients with permanent AF without intra-heart thrombi and hemodynamically not significant carotid bifurcation atherosclerotic stenosis. We performed echocardiography, 24-hours monitoring of electrocardiography (ECG), ultrasound of brachiocephalic arteries, sphygmography of common carotid arteries, computer tomography of the brain, hemostasiograms, lipid profile, hemoglobin A1c. According to the 24-hours ECG monitoring data, we divided patients into two groups up to the maximum pauses between ventricular complexes in AF: patients with a pause <1,5 seconds (113); ≥1,5 seconds (89). Both groups were on the same standard therapy including novel oral anticoagulants. We observed the patients during 1 year to analyze the verified stroke or transient ischemic attack (TIA).Results. In ultrasound, there was an increase of linear blood flow velocity in the area of carotid stenosis during the spread of the pulse wave after the long pause between ventricular contractions in group 2 up to 2,5 m/sec as in hemodynamically significant stenosis. In 1-year observation, there was the higher stroke in group 2.Conclusion. The appearance of stroke and TIA in AF is higher in patients who have 1,5 seconds and more of maximum duration pauses between ventricular contractions. The reason of cryptogenic stroke can be the atherosclerotic plaque defragmentation with further embolism, caused by additional mechanical impact of increased hemodynamical parameters of pulse wave after long pause between ventricular contractions.